1982
DOI: 10.1121/1.2020157
|View full text |Cite
|
Sign up to set email alerts
|

Listeners' identification of environmental sounds

Abstract: The purpose of this investigation was to determine if listeners can accurately identify various environmental sounds. A total of 40 sounds were recorded: (a) 20 animal sounds from four cows, cats, dogs, pigs, and sheep; (b) 12 inanimate sounds from four typewriters, car horns, and telephones; (c) four musical sounds from a flute, piano, guitar, and drum; and (d) four human sounds (/pʌ) from two female and two male speakers. A master tape containing the randomly arranged recordings was prepared and presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The majority of studies have examined the perception of complex sounds in their natural environment (e.g., Vicente & Burns, 1996) and results indicate that both adults (Lass, Eastham, Parrish , Scherbick, & Ralph , 1982;Keller & Stevens, 2004) and children (Jacko, 1996) can identify the source of environmental sounds. One assumption underlying these studies is that the sound produced during each event is unique and must be learned by the individual, implying that a taxonomy of nomic mappings requires as many sounds as there are objects and events.…”
Section: Identifying Nomic and Symbolic Mappingsmentioning
confidence: 99%
“…The majority of studies have examined the perception of complex sounds in their natural environment (e.g., Vicente & Burns, 1996) and results indicate that both adults (Lass, Eastham, Parrish , Scherbick, & Ralph , 1982;Keller & Stevens, 2004) and children (Jacko, 1996) can identify the source of environmental sounds. One assumption underlying these studies is that the sound produced during each event is unique and must be learned by the individual, implying that a taxonomy of nomic mappings requires as many sounds as there are objects and events.…”
Section: Identifying Nomic and Symbolic Mappingsmentioning
confidence: 99%
“…Beyond merely being a perceptual attribute of sound, timbre is known to play a primary role in the recognition, categorization, and identification of sound-producing events or sound sources when these sources are outside of the field of vision [ 1 3 ]. Converging evidence suggests that from quick evaluations about the source of the sound (e.g., [ 4 6 ]), to identifying a familiar person from their voice (e.g., [ 7 ]) or categorizing or identifying a music genre (e.g., [ 8 , 9 ]), healthy listeners are remarkably efficient at recognizing and identifying sounds. Anecdotally, people can also skillfully recognize and attend to sounds in the midst of rapidly changing auditory scenes in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while most listeners are familiar with the sounds of crashing cars and gunfire, only a small group may be exposed to these sounds in outdoor settings on a regular basis. Similarly, few urban dwellers have a chance to hear cows moo or roosters crow [10,12,89], but have no difficulties identifying them correctly. Thus, the "typical" context of these sounds is more often defined by the imagination of sound engineers than the actual context in which these sounds are heard in real-life.…”
Section: Environmental Soundsmentioning
confidence: 99%
“…Environmental sounds, being produced by naturally occurring physical sources, have complex acoustic structure that reflects aspects of their sources, as shown in studies of bouncing and breaking bottles [7], footsteps [8] and hand claps [9]. Many environmental sounds are also highly familiar -listeners can quickly and easily identify a wide range of environmental sounds [10][11][12][13]. Some studies have shown that environmental sounds share many features with speech in terms of the effects of varying spectral or temporal resolution, and the frequency region carrying the greatest information [12,14,15], and in a multifactorial study of a wide range of listening abilities the ability to identify environmental sounds tended to group with the ability to understand speech as opposed to more psychophysically oriented tasks [16].…”
Section: Introductionmentioning
confidence: 99%